The Effect of Marriage Age Limit Changes on Marriage Dispensation Granting by the Limboto Religious Court: Study of the Republic of Indonesia Constitutional Court Decision No. 22/PUU-XV/2017 - Karim, Fibriyanti (Fakultas Hukum Universitas Islam Jakarta, 2024)
Changes to the marriage age limit stipulated in the Marriage Law are an important policy expected to overcome early marriage and protect children's rights. This study aims to analyze the application of marriage dispensation in the Limboto Religious Court after the amendment of the Marriage Law and evaluate the impact of the Constitutional Court Decision No. 22/PUU-XV/2017 on the number of marriage dispensation applications. The method used is normative legal research with a case and law approach and interviews with Limboto Religious Court judges. The study results show that although the purpose of changing the marriage age limit is to reduce early marriage and protect children's rights, there has been an increase in marriage dispensation applications at the Limboto Religious Court. Social, economic, and cultural factors are the main causes of many marriage dispensation cases. In conclusion, although this policy has positive aims, its implementation has not been effective in reducing the number of child marriages. Therefore, this policy needs to be further evaluated, emphasizing a more comprehensive approach, such as community education, strengthening the capacity of judges, and providing social support.